2012
DOI: 10.1111/j.1365-294x.2012.05482.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and horizontal photobiont transmission within populations of a lichen symbiosis

Abstract: Lichens are widespread symbioses and play important roles in many terrestrial ecosystems. The genetic structure of lichens is the result of the association between fungal and algal populations constituting the lichen thallus. Using eight fungus- and seven alga-specific highly variable microsatellite markers on within-population spatial genetic data from 62 replicate populations across Europe, North America, Asia and Africa, we investigated the contributions of vertical and horizontal transmission of the photob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
126
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 103 publications
(124 reference statements)
3
126
0
Order By: Relevance
“…It has been previously shown that dispersal of vegetative propagules is spatially limited in L. pulmonaria (Walser 2004), and the present work of Dal Grande et al (2012) shows that the signal for vertical transmission is cut in half over distances of 10 m. Vegetative propagules represent minute thallus initials that are larger, heavier and less aerodynamic than fungal spores. However, vertical transmission conveys clear advantages, including bypassing the bottleneck of biont resynthesis and, once established and producing sexual structures, opening the possibility for experimentation with new biont lineages under new microhabitat conditions.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…It has been previously shown that dispersal of vegetative propagules is spatially limited in L. pulmonaria (Walser 2004), and the present work of Dal Grande et al (2012) shows that the signal for vertical transmission is cut in half over distances of 10 m. Vegetative propagules represent minute thallus initials that are larger, heavier and less aerodynamic than fungal spores. However, vertical transmission conveys clear advantages, including bypassing the bottleneck of biont resynthesis and, once established and producing sexual structures, opening the possibility for experimentation with new biont lineages under new microhabitat conditions.…”
mentioning
confidence: 87%
“…These different dispersal strategies ostensibly shape the population genetic structure of lichen symbioses, but the relative contributions of vertical (joint) and horizontal (independent) symbiont transmission have long eluded lichen evolutionary biologists. In this issue of Molecular Ecology, Dal Grande et al (2012) close in on this question with the lung lichen, Lobaria pulmonaria, a flagship species in the conservation of old growth forests. By capitalizing on available microsatellite markers for both fungal and algal symbionts, they show that while vertical transmission is the predominant mode of reproduction, horizontal transmission is demonstrable and actively shapes population genetic structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lichen, which are symbiotic associations between fungi and photosynthetic partners (algae and/or cyanobacteria), are another mixed case. Many lichen combine an asexual mode of reproduction in which propagules are made that contain samples of both partners, with sexual reproduction by the fungus through release of spores which, on germination, must find a compatible photosynthetic partner (29). A lichen then reproduces as a single unit when in asexual mode but not when the fungus reproduces sexually.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…ITS phylogenies are based on only one locus, but genetic diversity at the subspecific level is best explored with a multilocus approach. Fingerprinting techniques can provide valuable data on the genetic diversity of populations and these have been successfully used for characterizing lichen-forming fungi at the subspecific level: microsatellite-based fingerprinting (Walser et al 2003;Walser et al 2005;Werth et al 2006;Werth et al 2007;Widmer et al 2010;Mansournia et al 2011;Dal Grande et al 2012), tRNA fingerprinting (Schmitt et al 2002), or randomly amplified polymorphic DNA (RAPD) analysis applied to either pure fungal material such as central strands of Usnea sp. (Heibel et al 1999) or apothecial discs (Printzen et al 1999), or to sterile cultured fungal isolates (Murtagh et al 1999;Dyer et al 2001;Honegger et al 2004b;Honegger & Zippler 2007;Itten & Honegger 2010).…”
Section: Introductionmentioning
confidence: 99%